URGENSI ITIKAD BAIK DALAM PERJANJIAN PINJAMAN UANG KREDIT TERKAIT DENGAN PASAL 1338 AYAT ( 3) KUH PERDATA DIKOPERASI PERIKANAN “SUMBER TANI NELAYAN”, SAMARINDA SEBERANG - Andi Saharudin (Universitas 17 Agustus 1945 Samarinda, 2013)
AbstrackAgreement borrowing money should be conducted in good faith . Good faith is very closely related to the execution of agreement borrowing money . At the start time of executing the agreement timbullan assortment of issues that need to be done , because this is very important in good faith in carrying out the agreement . Implementation of the agreement is also dependent on the honesty of a person to comply with the agreement . If the agreement is done in bad faith ( bad faith ) such agreement has been violated norms of good faith determines that the agreement must be executed in good faith .In the implementation of the agreement in good faith to be run in human hearts one must remember , that the man was a member of the community should be away from the deceptive nature of the other party . Sanagt good faith in the execution of the agreement is important because in good faith then someone will believe the lain.Para the parties to the agreement should avoid the implementation of the agreement in bad faith . If this happens then the aggrieved may submit a claim to court . As state law , every citizen gained an equal footing in the law so that every citizen thus protected by hukum.Dengan occur close relationship between the doctrine of good faith in the execution of the agreement and the theory of confidence at the time of the agreement . Good faith ( Article 1338 , paragraph 3 ) and propriety ( section 1339 ) is generally mentioned in the same breath , if the judge after examining the appropriateness of an agreement can not be implemented then it means that the agreement was contrary to public order and decency .